TGF-β2 Induces Gli1 in a Smad3-Dependent Manner Against Cerebral Ischemia/Reperfusion Injury After Isoflurane Post-conditioning in Rats - Peng, Li; Yang, Chengwei; Yin, Jiangwen; Ge, Mingyue; Wang, Sheng; Zhang, Guixing; Zhang, Qingtong; Xu, Feng; Dai, Zhigang; Xie, Liping; Li, Yan; Si, Jun-qiang; et al. (Frontiers in Neuroscience, 2019)
Isoflurane (ISO) post-conditioning attenuates cerebral ischemia/reperfusion (I/R) injury, but the underlying mechanism is incompletely elucidated. Transforming growth factor beta (TGF-β) and hedgehog (Hh) signaling pathways govern a wide range of mechanisms in the central nervous system. We aimed to investigate the effect of the TGF-β2/Smad3 and sonic hedgehog (Shh)/ Glioblastoma (Gli) signaling pathway and their crosstalk in the hippocampus of rats with ISO post-conditioning after cerebral I/R injury. Adult male Sprague-Dawley rats were subjected to middle cerebral artery occlusion (MCAO), 1.5h occlusion and 24h reperfusion (MCAO/R). To assess the effect of ISO after I/R injury, various approaches were used, including neurobehavioral tests, TTC staining, HE staining, Nissl staining, TUNEL staining, immunofluorescence (IF), qRT-PCR (quantitative real-time polymerase chain reaction) and Western blot. The ISO post-conditioning group (ISO group) received 1hour ISO post-conditioning when reperfusion was initiated, leading to lower infarct volumes and neurologic deficit scores, more surviving neurons, and less damaged and apoptotic neurons. IF staining, qRT-PCR and Western blot showed high expression levels of TGF-β2, Shh and Gli1 in the hippocampal CA1 of the ISO group. Phosphorylated Smad3 (p-Smad3), Patched (Ptch), and Smoothed (Smo) were also increased at protein level in the ISO group, whereas total Smad3 expression did not change in all groups. When TGF-β2 inhibitor pirfenidone or Smad3 inhibitor SIS3 HCl was administered, the expression levels of p-Smad3 and Gli1 were reduced, and surviving pyramidal neurons decreased. By contrast, the expression levels of TGF-β2 and p-Smad3 did not change significantly after pre-injection of Smo inhibitor cyclopamine, but reduced the expression levels of Shh, Ptch and Gli1. Moreover, Gli showed the lowest expression levels with pirfenidone combined with cyclopamine. These findings indicate that the TGF-β and hedgehog signaling pathways mediate the neuroprotection of ISO post-conditioning after cerebral I/R injury, and crosstalk between two pathways at the Gli1 level.